Queering contemporary Asian American art - Kina, Laura; Bernabe, Jan Christian (Seattle University of Washington Press, 2017)
Queering Contemporary Asian American Art takes Asian American differences as its point of departure, and brings together artists and scholars to challenge normative assumptions, essentialisms, and methodologies within Asian American art and visual culture. Taken together, these nine original artist interviews, cutting-edge visual artworks, and seven critical essays explore contemporary currents and experiences within Asian American art, including the multiple axes of race and identity, queer bodies and forms, kinship and affect, and digital identities and performances.Using the verb and critical lens of “queering” to capture transgressive cultural, social, and political engagement and practice, the contributors to this volume explore the connection points in Asian American experience and cultural production of surveillance states, decolonization and diaspora, transnational adoption, and transgender bodies and forms, as well as heteronormative respectability, the military, and war. The interdisciplinary and theoretically informed frameworks in the volume engage readers to understand global and historical processes through contemporary Asian American artistic production.
Keywords: Asian American art -- 21st century; Group identity in art; Art and society -- United States -- History -- 21st century